FEMALE SPACE AND IDENTITY CHALLENGES IN NIGERIAN DRAMA: A STUDY OF AMIRIKPA OYIGBENU’S TOWN HALL WHISPERS AND JONATHAN MBACHAGA’S WIDOWS’ MIGHT - Suswam , Sonia Sewuese; Daniel , James Chikada (International Journal of Allied Sciences (IJAS), 2025)
Feminist Theater is a reaction against patriarchal values that are used to undermine and disempower women in the society. Its aim is to combat negative trends through which the female gender has been dominated, marginalized and dehumanized. As such, gender advocates have challenged patriarchal norms through the representation of strong, vibrant, resilient, and unflattering female characters who are anxious to break-free from cultural oppression and expand their scope beyond the space allotted them by the society. It is on this backdrop that the paper sets out to amplify the role of Feminist Theater in redressing the debased status of women in Nigerian society. Using the Social Feminists Theory as a paradigm to analyze the selected plays, Town Hall Whispers by Amirikpa Oyigbenu and Widows Might by Jonathan Mbachaga. The study found that women are aggrievedly subjugated in society and recommends that the, position of the female space should be redefined to accommodate women contributing their unique skills to nation-building.